Postcolectomy Peritoneal Environment Increases Colon Cancer Cell Migration Capacity - Liron Berkovich; Ronen Ghinea; Salem Majdop; Baruch Shpitz; Ian White; Moshe Mishaeli; Shmuel Avital (Gastroenterology Research and Practice)
Background. Clinical data and animal models support an association between postoperative inflammatory response and the risk of colorectal cancer recurrence. Our aim was to evaluate postoperative peritoneal inflammation and its impact on cultured colon cancer cells’ migration capacity. Methods. 23 patients undergoing elective colorectal resection with uneventful recovery were prospectively enrolled. Patients were operated on for both malignant and benign etiologies. Peritoneal fluids collected at surgery initiation and after surgery were evaluated for their effect on migration potential of human colon cancer cells using an in vitro scratch assay and on TNF-α, IL-1β, IL-6, and IL-10 levels using bead-based fluorokine-linked multianalyte profiling. Results. Postoperative peritoneal fluid from all patients increased the migration capacity of colon cancer cells compared to preoperative levels. This effect was significant during the first two postoperative days and decreased thereafter. The increase in colon cancer cell migration capacity correlated with increased levels of peritoneal TNF-α and IL-10. Conclusion. In this pilot study, we have demonstrated that the intraperitoneal environment following colorectal resection significantly enhances colon cancer cells migration capacity. This effect is associated with postoperative intra-abdominal cytokines level. A larger scale study in colorectal cancer patients is needed in order to correlate these findings with perioperative parameters and clinical outcome.